Customer Engagement Analysis as Mediating the Influence on Social Media Marketing of Purchase Intentions on Skincare Avoskin - Chreisna Wicaksono Perkasa; Adam Faritzal (Universitas Bina Darma, 2022)
This research aims to analyze customer engagement in mediating the influence of social media marketing on purchase intentions. The approach used in this study is quantitative; the population of this study is all users of Avoskin skincare products in Bandung. Data is analyzed by testing the validity, reliability, and inner model using smartPLS. The results showed a direct influence of social media marketing activities on purchase intentions in Avoskin skincare users in Bandung, and customer engagement can mediate the influence of social media marketing activities on purchase intentions.